Adherence to the ‘Atrial Fibrillation Better Care’ Pathway in Patients with Atrial Fibrillation: Impact on Clinical Outcomes—A Systematic Review and Meta-Analysis of 285,000 Patients - Romiti, Giulio Francesco; Pastori, Daniele; Rivera-Caravaca, José Miguel; Ding, Wern Yew; Gue, Ying Xuan; Menichelli, Danilo; Gumprecht, Jakub; Kozieł, Monika; Yang, Pil-Sung; Guo, Yutao; Lip, Gregory Y.H.; Proietti, Marco (Thrombosis and haemostasis, 2022)
Abstract Objective The ‘Atrial fibrillation Better Care’ (ABC) pathway has been recently proposed as a holistic approach for the comprehensive management of patients with atrial fibrillation (AF). We performed a systematic review of current evidence for the use of the ABC pathway on clinical outcomes. Methods and Results We performed a systematic review and meta-analysis according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. PubMed and EMBASE were searched for studies reporting the prevalence of ABC-pathway-adherent management in AF patients, and its impact on clinical outcomes (all-cause death, cardiovascular death, stroke, and major bleeding). Meta-analysis of odds ratio (OR) was performed with random-effects models; subgroup analysis and meta-regression were performed to account for heterogeneity. Among the eight studies included, we found a pooled prevalence of ABC-adherent management of 21% (95% confidence interval, CI: 13–34%), with a high grade of heterogeneity, explained by the increasing adherence to each ABC criterion. Patients treated according to the ABC pathway showed a lower risk of all-cause death (OR: 0.42; 95% CI: 0.31–0.56), cardiovascular death (OR: 0.37; 95% CI: 0.23–0.58), stroke (OR: 0.55; 95% CI: 0.37–0.82) and major bleeding (OR: 0.69; 95% CI: 0.51–0.94), with moderate heterogeneity. Prevalence of comorbidities was moderators of heterogeneity for all-cause and cardiovascular death, while longer follow-up was associated with increased effectiveness for all outcomes. Conclusion Adherence to the ABC pathway was suboptimal, being adopted in one in every five patients. Adherence to the ABC pathway was associated with a reduction in the risk of major adverse outcomes.